ANALISIS SISTEM MANAJEMEN TERHADAP POLA SELEKSI PENERIMAAN CALON GURU DI SDIT AN-NIDA KOTA LUBUKLINGGAU - Handayani, Handayani; Widodo, Slamet (Journal of Professional Elementary Education, 2024)
The teacher acceptance mechanism gets the main attention, because at this stage of acceptance, you can choose and select prospective teachers according to the desired criteria. Schools need to make a good teacher recruitment management recruitment to support the teaching and learning process. This study aims to determine the planning, implementation, control and evaluation of teachers at SDIT Annida Lubuklinggau. This study uses a qualitative approach with a qualitative descriptive method. The research subjects consisted of the principal, the board of teachers and staff, the guardians of SDIT Annida Lubuklinggau students. Data collection consists of observation, interviews and documentation. Data analysis techniques include editing, categories, displaying data and storage. The conclusions in this study, namely planning for teacher admissions at SDIT Annida Lubuklinggau went well, namely recruiting teachers by selecting the administration of job applications and testing the ability to read the Al-Qur’an as well as micro teaching tests.